2015
DOI: 10.1186/s40809-015-0010-1
|View full text |Cite
|
Sign up to set email alerts
|

Swirls and spots: relationship between qualitative and quantitative hematoma heterogeneity, hematoma expansion, and the spot sign

Abstract: Background: Acute intracerebral hemorrhage (ICH) heterogeneity on NCCT, characterized by qualitative and quantitative methods, is predictive of hematoma expansion and mortality however association with the spot sign is not well-described. We sought to validate and determine the association between qualitative and quantitative hematoma heterogeneity with expansion and the spot sign, respectively. Methods: We retrospectively studied 71 ICH patients presenting <24 h post-ictus with baseline NCCT, CTA and 24-hour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…7,39 Connor and colleagues retrospectively assessed the presence of density heterogeneity and spot sign in 71 patients. 39 The authors found that the presence of hypodensities was independently associated with hemorrhage-expansion but did not investigate the spatial correlation between spots and hypodense regions on NCCT. In a subanalysis of a work investigating hypodensities as a marker of hemorrhage-growth, we randomly selected 40 patients with both spot sign(s) and hypodensities.…”
Section: Ncct Biomarkers Of the Risk Of Hemorrhage-expansionmentioning
confidence: 99%
“…7,39 Connor and colleagues retrospectively assessed the presence of density heterogeneity and spot sign in 71 patients. 39 The authors found that the presence of hypodensities was independently associated with hemorrhage-expansion but did not investigate the spatial correlation between spots and hypodense regions on NCCT. In a subanalysis of a work investigating hypodensities as a marker of hemorrhage-growth, we randomly selected 40 patients with both spot sign(s) and hypodensities.…”
Section: Ncct Biomarkers Of the Risk Of Hemorrhage-expansionmentioning
confidence: 99%
“…2025 Other studies have reported that an irregular shape or the heterogeneity of a hematoma (ie, the presence of a “blend sign”) can be helpful. 21,2629 …”
mentioning
confidence: 99%
“…Irregular ICH shape (but not density) was found to be independently associated with poor outcome in a retrospective study of over 2000 patients . Validation studies of qualitative and quantitative densitometry measures as predictors of outcome, the presence of CTA spot sign and ICH growth have been performed in different patient cohorts . More attention to the reporting of ICH density (homogeneous/heterogeneous) and shape (regular/irregular) is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…26 Validation studies of qualitative and quantitative densitometry measures as predictors of outcome, the presence of CTA spot sign and ICH growth have been performed in different patient cohorts. 25,27,35 More attention to the reporting of ICH CT angiography is being increasingly applied in the imaging assessment of acute ICH, most often in comprehensive stroke centres, particularly in patients presenting within 6 h of ictus. The CTA spot sign has been identified as an independent predictor of ICH growth and outcome 36 and is representative of dynamic haemorrhage due to the active contrast extravasation into an expanding haematoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation